2022
DOI: 10.12998/wjcc.v10.i15.5119
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of arytenoid cartilage dislocation after tracheal intubation in the intensive care unit: A case report

Abstract: BACKGROUND Arytenoid cartilage dislocation is a rare and often overlooked complication of tracheal intubation or blunt laryngeal trauma. The most common symptom is persistent hoarseness. Although cases of arytenoid dislocation due to tracheal intubation are reported more frequently in otolaryngology, reports on its occurrence in the intensive care unit (ICU) are lacking. We report a case of delayed diagnosis of arytenoid cartilage dislocation after tracheal intubation in the ICU. CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Patients in the intensive care unit may be at a greater risk of AD due to prolonged tracheal intubation, difficult intubation, nasogastric tube insertion, anemia, chronic steroid use, and low BMI. [ 7 ] In our cohort, the patients who underwent liver transplantation had prolonged tracheal intubation and the presence of a nasogastric feeding tube, indicating that the persistent pressure exerted by tracheal tubes or nasogastric tubes is a possible cause of AD. An animal study indicated that the tracheal tube could exert pressure in the region of the arytenoid cartilage when the tracheal tube was left in situ.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Patients in the intensive care unit may be at a greater risk of AD due to prolonged tracheal intubation, difficult intubation, nasogastric tube insertion, anemia, chronic steroid use, and low BMI. [ 7 ] In our cohort, the patients who underwent liver transplantation had prolonged tracheal intubation and the presence of a nasogastric feeding tube, indicating that the persistent pressure exerted by tracheal tubes or nasogastric tubes is a possible cause of AD. An animal study indicated that the tracheal tube could exert pressure in the region of the arytenoid cartilage when the tracheal tube was left in situ.…”
Section: Discussionmentioning
confidence: 98%
“…[5,6] If left untreated, undiagnosed, or misdiagnosed, AD could lead to hypermobile joint or ankylosis of the affected cricoarytenoid joint (CAJ). [7] The underlying mechanisms of AD are still elusive. Previous studies suggested that direct trauma by a laryngoscope or intubation tube is responsible for dislocation of the CAJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation